A phenomenological ground for relational perception. Issue 5 (20th October 2022) - Akoury, Chahid
Abstract : Relational perception is a cognitive act enabling users to both epistemically handle a given object and ontologically reason about it. The condition for such a perceptive act is fully dependent on an understanding of support relations and knowledge of the situation at hand. Such knowledge according to this article is present and afforded by a ground condition. According to James J. Gibson the ground is what supports the survival of the animal. In other words, the discoverability of the environment, its textures and surfaces, and therefore the animal's abilities to navigate and interact with it relies strictly on perception. Additionally, this article posits the importance of relational perception in experiencing artistic practices. It presents a strong argument in support of a philosophy of becoming, where aesthetics, materiality, and haptic relations, are interweaved and experienced as an architected landscape. In this regard, artworks are not simply viewed, but become lived space, as they afford an amalgamation of mental constructs and affective phenomenological experiences.